Answer:
y=14; x=72
Step-by-step explanation:
y=(21×2)/3; x=(48×21)/14
Simplify the expression:
8(2x - 3) - 6x = 8×2x - 8×3 - 6x = 16x - 24 - 6x = 10x - 24
for x=3
put value of "x" to the expression:
<u>10×3 - 24 = 30 - 24 = 6</u>
Answer:
![\frac{\cos\left(2x\right)-\cos\left(4x\right)}{\sin\left(2x\right)+\sin\left(4x\right)}=\tan\left(x\right)](https://tex.z-dn.net/?f=%5Cfrac%7B%5Ccos%5Cleft%282x%5Cright%29-%5Ccos%5Cleft%284x%5Cright%29%7D%7B%5Csin%5Cleft%282x%5Cright%29%2B%5Csin%5Cleft%284x%5Cright%29%7D%3D%5Ctan%5Cleft%28x%5Cright%29)
Step-by-step explanation:
![\frac{\cos\left(2x\right)-\cos\left(4x\right)}{\sin\left(2x\right)+\sin\left(4x\right)}](https://tex.z-dn.net/?f=%5Cfrac%7B%5Ccos%5Cleft%282x%5Cright%29-%5Ccos%5Cleft%284x%5Cright%29%7D%7B%5Csin%5Cleft%282x%5Cright%29%2B%5Csin%5Cleft%284x%5Cright%29%7D)
Apply formula:
and
![\sin\left(A\right)+\sin\left(B\right)=2\cdot\sin\left(\frac{A+B}{2}\right)\cdot\sin\left(\frac{A-B}{2}\right)](https://tex.z-dn.net/?f=%5Csin%5Cleft%28A%5Cright%29%2B%5Csin%5Cleft%28B%5Cright%29%3D2%5Ccdot%5Csin%5Cleft%28%5Cfrac%7BA%2BB%7D%7B2%7D%5Cright%29%5Ccdot%5Csin%5Cleft%28%5Cfrac%7BA-B%7D%7B2%7D%5Cright%29)
We get:
![=\frac{-2\cdot\sin\left(\frac{2x+4x}{2}\right)\cdot\sin\left(\frac{2x-4x}{2}\right)}{2\cdot\sin\left(\frac{2x+4x}{2}\right)\cdot\cos\left(\frac{2x-4x}{2}\right)}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B-2%5Ccdot%5Csin%5Cleft%28%5Cfrac%7B2x%2B4x%7D%7B2%7D%5Cright%29%5Ccdot%5Csin%5Cleft%28%5Cfrac%7B2x-4x%7D%7B2%7D%5Cright%29%7D%7B2%5Ccdot%5Csin%5Cleft%28%5Cfrac%7B2x%2B4x%7D%7B2%7D%5Cright%29%5Ccdot%5Ccos%5Cleft%28%5Cfrac%7B2x-4x%7D%7B2%7D%5Cright%29%7D)
![=\frac{-\sin\left(\frac{2x-4x}{2}\right)}{\cos\left(\frac{2x-4x}{2}\right)}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B-%5Csin%5Cleft%28%5Cfrac%7B2x-4x%7D%7B2%7D%5Cright%29%7D%7B%5Ccos%5Cleft%28%5Cfrac%7B2x-4x%7D%7B2%7D%5Cright%29%7D)
![=\frac{-\sin\left(\frac{-2x}{2}\right)}{\cos\left(\frac{-2x}{2}\right)}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B-%5Csin%5Cleft%28%5Cfrac%7B-2x%7D%7B2%7D%5Cright%29%7D%7B%5Ccos%5Cleft%28%5Cfrac%7B-2x%7D%7B2%7D%5Cright%29%7D)
![=\frac{-\sin\left(-x\right)}{\cos\left(-x\right)}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B-%5Csin%5Cleft%28-x%5Cright%29%7D%7B%5Ccos%5Cleft%28-x%5Cright%29%7D)
![=\frac{-\cdot-\sin\left(x\right)}{\cos\left(x\right)}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B-%5Ccdot-%5Csin%5Cleft%28x%5Cright%29%7D%7B%5Ccos%5Cleft%28x%5Cright%29%7D)
![=\frac{\sin\left(x\right)}{\cos\left(x\right)}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B%5Csin%5Cleft%28x%5Cright%29%7D%7B%5Ccos%5Cleft%28x%5Cright%29%7D)
![=\tan\left(x\right)](https://tex.z-dn.net/?f=%3D%5Ctan%5Cleft%28x%5Cright%29)
Hence final answer is
![\frac{\cos\left(2x\right)-\cos\left(4x\right)}{\sin\left(2x\right)+\sin\left(4x\right)}=\tan\left(x\right)](https://tex.z-dn.net/?f=%5Cfrac%7B%5Ccos%5Cleft%282x%5Cright%29-%5Ccos%5Cleft%284x%5Cright%29%7D%7B%5Csin%5Cleft%282x%5Cright%29%2B%5Csin%5Cleft%284x%5Cright%29%7D%3D%5Ctan%5Cleft%28x%5Cright%29)
Answer:
<h2>Model B</h2>
Step-by-step explanation:
The model needs to show 1.8 because 2 x 0.9 = 1.8. Model B is the only model that shows this.
<em>Hope this helps</em>